Ecogeography of roe deer: relation with other ungulates in sympatry - Torres, Rita Maria Tinoco da Silva (2012)
Understanding the spatial distribution of organisms is a central topic in ecology. The European roe deer (Capreolus capreolus) population is in Portugal and Norway at the southwestern and northern edge of its distribution, respectively. Understanding the factors that act on these populations enlightens both local aspects concerning their conservation and wider scale aspects of the species bioclimatic envelope, which is crucial for being better able to predict the impacts of environmental change. The main aim of this thesis was to evaluate roe deer distribution in Portugal and Norway, two countries with contrasting landscapes, seasonality and with different anthropogenic pressure. The interspecific relationship with sympatric ungulates was also analysed. By using pellet group counts, we investigated habitat use of roe deer, identifying the major environmental descriptors, to understand the importance of forest structure, vegetation characteristics, landscape structure and human disturbance on their distribution. The analyses were based on presence – absence data and were carried out at two spatial scales. The results showed that habitat use of roe deer was different across countries. In Portugal, at the local scale, roe deer distribution was positively associated with high density of shrubs, especially heather and brambles, while the presence of red deer had a negative effect on their distribution. At a broad scale, roe deer was negatively associated with spatial heterogeneity, namely mean shape index and made less use of areas close to agricultural fields. In Norway, at the local scale, roe deer made more use of areas with high cover of deciduous trees and patches containing juniper and Vaccinium sp.. At a broad scale, roe deer use patches near edges between fields and forest. In both countries, roe deer make use of areas further away from roads. While in Norway roe deer in both summer and winter are always close to houses, in Portugal they are either far (summer) or indifferent (winter). Anthropogenic disturbance is better tolerated in Norway, where the importance of the critical season seems to be higher. Human disturbance may contribute to roe deer habitat loss in Portugal, while roe deer are able to persist close to humans in managed landscapes in Norway. In fact, some of the differences observed could be more due to the indirect impacts of human exploitation (e.g. presence of free-ranging dogs and hunting regulation) rather than the actual human presence or land-use per se. I conclude that the methodology and tools developed here are readily expandable to address similar questions in different contexts. Wildlife management would benefit greatly from a more holistic/integrative approach and that should include human aspects, as human disturbance is expected to continue increasing.